ANALYSIS OF INDICATORS OF THE TOURISM INDUSTRY IN UKRAINE AND THE WORLD: PROBLEMS AND DEVELOPMENT PROSPECTS (Development Service Industry Management, 2023)
Analysis of current trends in the development of the tourism industry in Ukraine shows that starting from 2020, tourism sector enterprises were constantly under negative pressure from external factors. Thus, measures to overcome the consequences of the COVID-2019 pandemic caused significant damage to the development of the tourism business in Ukraine, which significantly complicated the procedures for moving citizens both within a certain country and the possibility of international tourism due to the introduction of significant "covid" restrictions on the movement of citizens between countries. In particular, as a result of the policy of restrictions on entry into the countries of the European Union, the tourism sector of many countries suffered significant losses during 2020-2022. According to UNWTO estimates, measures to overcome the 2019 COVID-2019 pandemic in 2020-2021 led to a significant drop in volumes (60%-80%) of international tourism, and the decrease in revenues from the export of tourist services amounted to approximately 910 billion - 1.2 trillion US dollars. The purpose of the study is to summarize the current trends in the development of the tourism industry in Ukraine and the world in order to systematize the factors that have a negative impact on the tourism industry and develop measures to implement the "post-conflict tourism" program in Ukraine. In the conditions of globalization, the tourism industry is gaining more and more importance, which defines it as one of the most promising branches of global export in the world. The average annual growth rate of the global tourism industry averaged about 5% per year. According to UNWTO statistics, by 2022 the tourism industry will provide approximately 10% of gross global income and every tenth job in the world will be directly or indirectly generated by tourism. However, the global crisis caused by the COVID-19 pandemic, as well as the growth of political, social and military instability in certain regions, caused significant damage to the economy of the tourism sector, which led to negative consequences for all representatives of the entire tourism chain (tour operators, travel agencies, carriers , hoteliers, restaurateurs, etc.). Statistics show a significant drop in the functioning of tourism enterprises in Ukraine in 2022 as a result of the aggression of the Russian Federation. In particular, it is possible to note a drop of 28% in the total number of taxpayers in the tourism sector. In addition, the number of legal entities decreased by 36%, and individuals by 24.5%. As a result, there was a significant decrease in the amount of taxes paid by representatives of the tourist business community by 33.3%, as well as a 12.9% decrease in the payment of the tourist tax.The priority tasks of representatives of state institutions responsible for the development of the tourism industry in Ukraine, as well as representatives of the tourism business community, include the need to develop a post-conflict tourism program taking into account the international experience of individual countries and domestic realities.
Keywords: tourism; post-conflict tourism; tourism industry; COVID-19